2007
DOI: 10.1111/j.1349-7006.2007.00485.x
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference‐mediated signal transducers and activators of transcription 3 gene silencing inhibits invasion and metastasis of human pancreatic cancer cells

Abstract: Signal transducers and activators of transcription-3 (STAT3), a central cytoplasmic transcription factor, is frequently overexpressed and constitutively activated by tyrosine during malignant transformation. The overexpression and phosphorylation of STAT3 in pancreatic cancer has been described only recently, but the roles and mechanism still remain unclear. In this study, we elucidate the significance of the STAT3 signaling pathway in metastatic potentials of pancreatic cancer. We stably silence the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 36 publications
2
50
0
1
Order By: Relevance
“…In breast cancer, gastric cancer and hepatocellular carcinoma, STAT3 signaling controls VEGFA expression (4,5,14). In pancreatic cancer, STAT3 signaling regulates the expression of MMP2 (15), and in human melanoma brain metastases, activated Stat3 regulates the expression of FGF2 (3). These results demonstrate that constitutive STAT3 signaling contributes to tumor angiogenesis through multiple mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In breast cancer, gastric cancer and hepatocellular carcinoma, STAT3 signaling controls VEGFA expression (4,5,14). In pancreatic cancer, STAT3 signaling regulates the expression of MMP2 (15), and in human melanoma brain metastases, activated Stat3 regulates the expression of FGF2 (3). These results demonstrate that constitutive STAT3 signaling contributes to tumor angiogenesis through multiple mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that STAT3 directly regulates vascular endothelial growth factor A (VEGFA) expression to induce tumor angiogenesis in breast cancer, gastric cancer and hepatocellular carcinoma (4,5,14). In pancreatic cancer, STAT3-targeting RNA interference (RNAi) inhibits angiogenesis by suppressing the expression of matrix metalloproteinase-2 (MMP2) (15). In human melanoma brain metastases, activated STAT3 contributes to tumor angiogenesis by regulating the expression of basic fibroblast growth factor (FGF2) (3).…”
mentioning
confidence: 99%
“…STAT signaling is critical for normal cellular processes such as embryonic development, organogenesis and organ function, innate and adaptive immune function, regulation of cell differentiation, growth, and apoptosis [122][123][124][125][126][127]. In normal cells, STAT3 protein activation is strictly controlled to prevent unscheduled gene regulation, while constitutive activation of STAT3 has been detected in a wide number of human cancer cell lines and primary tumors, such as 50% of HCC, leukemias, lymphomas, multiple myelomas, prostate, gastric, breast, lung, and head and neck cancer [128][129][130][131][132][133][134].…”
Section: Activation Of Stat3mentioning
confidence: 99%
“…Correlative associations between FAS expression and poor prognosis for patients were also observed in non-hormonedependent cancers (69)(70)(71) as well as with metastasis (72).…”
Section: Implication Of Fatty Acid Synthasementioning
confidence: 81%